Community involvement in culture and nature tourism in Sarawak. - Spencer Empading Sanggin (Universiti Kebangsaan Malaysia, 2009)
Tourism has gained recognition as one of the fastest growing industry in Malaysia and generated substantial revenue to the country. In Sarawak local cultures have long been the main tourism attractions together with adventure, and lately the focus of tourism in Sarawak include nature. Tourism programs if properly planned and implemented can and should bring benefits not only to the tour operators and the local communities, but also helps to conserve the environment. Nevertheless, there are some essential issues that must be tackled in order to ensure the sustainability of tourism in Sarawak. The success and sustainability of ecotourism depends to a large extend on the participation and cooperation from the local people in the planning and management of tourism activities. This article explores these two vital issues within the context of sustainable tourism development in Sarawak. Studies indicated terms of employment, tourism generally provides both full-time as well as part-time employment for the local communities such providing river transportation and related services, and employment in the parks and hotels (as in the case of Mulu) in addition to providing cultural shows and performances as well as making and/or selling local handicrafts. The rate of local participation was higher among the more established tourism longhouses. Also, good but varied degree of cooperation exists between the local indigenous community and tour agencies. Consequently, the well-established tourism longhouses were generating more incomes through tourism when compared to the newly adopted longhouses.